Faktor Kebudayaan Pendorong Munculnya Loyalitas pada Konsumen Kuliner Kota Kediri Jawa Timur - Febriani, Nufian Susanti (Faculty of Communications Science, Dr. Soetomo University, 2017)
There is a trend in the city of Kediri which shows that culinary business that started from the â€œbedagâ€/roadside â€œrombongâ€ have loyal customers while culinary business with established artifacts able to retain consumers not more than 1 year. This quantitative research using survey method with semantic diferential scale to collect data so that can be found a comprehensive picture of the population that is culinary consumers kediri city with an area of â€‹â€‹63.40 km2. The results showed that there is a significant influence on cultural factors on consumer loyalty. This research can be used as a reference for prospective investors who want to invest in Kediri city, especially in culinary field to use original cultural element of Kediri as one of marketing strategy to get consumer loyalty.